Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Dan Kepatuhan Diit Hipertensi Pada Lanjut Usia Di Desa Wironanggan Kecamatan Gatak Sukoharjo - SAPUTRI, Yuli Indah; , H.M. Abi Muhlisin, SKM. , M.Kep; , Agustaria Budinugroho S. kep., Ns (2015)
The case of hypertension incident of elderly in Wironaggan village 2014 is highest compared to other diseases recorded 206 patients. The high incidence of hypertension caused is still bad compliance hypertension diet,, and poor hypertension diet as a result of elderly lack knowledge. Health education is one way to increase knowledge of elderly through a speech method and media leaflets .The purpose of study is to know the influence of health education on knowledge and hypertension diet, compliance of elderly in Wironanggan Village of Gatak Sukoharjo. The research was using quasi experiment, and pretest - posttest with control groups design. Sampel research are 33 elderly of posyandu members and as case group and 33 elderly as control groups. Taking sample was using proportional random sampling. Health education was using speech method, instrument with Health education and leaflet. Instrument was using hypertension diet a questionnaire knowledge, and diet, hypertension compliance. Analysis data was using comparative data. The test results shows that Wilcoxon Sign Test a pre test post test of knowledge with p = 0.015. Results study showed with paired sample test pre test post test hypertension diet, p = 0,445. conclusions there was an influence of health education on knowledge but there was no influence of health education of hypertension diet, compliance of elderly, thus still needed behavioral discipline of elderly to follow hypertension diet, to avoid the recurrence of hypertension.